Keeping good teachers - Scherer, Marge, 1945- (Association for Supervision and Curriculum Development, 2003)
What attracts good teachers and keeps them in the profession? What makes schools better places for students to learn and for teachers to work? These questions are at the heart of Keeping Good Teachers. To answer them, many of the authors in this book have surveyed fellow educators to find out which practices and policies are most beneficial and practical to implement in schools. The book is divided into five sections:. Part I explores the extent of the teacher shortage and sets the context for studying it. Part II concentrates on induction, tackling the issue of how new teachers should be intr.